Biological Markers in River Catfish, Mystus Nemurus (C&V) Exposed to Hydrogen Sulphide - Hoque, Muhammad Tafazzal (1997)
Biochemical, histopathological, histochemical and bioenergetic parameters were studied to determine their suitability as biological markers for hydrogen sulphide toxicity detection using the river catfish Mystus nemurus (C&V) exposed to H2S in laboratory experiments as well as those caught from the wild. In the laboratory, the toxic effects of H2S to M nemurus juveniles were determined by using a flow-through bioassay technique. The 96-h LC₅₀ value of unionized H₂S was 3.20 µg/L, and 0.003 µg/L unionized H₂S was recommended as the safety level for M nemurus juveniles under tropical environmental condition. Sulphaemoglobin and thiosulphate concentrations significantly increased (p<0.01) with increasing hydrogen sulphide (H₂S) concentrations and exposure time. However, H₂S reduced the oxygen carrying capacity of haemoglobin by reducing oxyhaemoglobin. Glutathione S-transferase (GST) specific activities significantly increased (p<0.01) in fish exposed to H₂S higher than 30% of LC₅₀. Gill lesions such as epithelial separation, club-shaped lamellae and interlamellar fusion were observed at different concentrations of H2S. The evidence of neurotoxicity was elucidated by necrosis and damaged mitochondria in fish brain tissue. Sulphur accumulation in gills progressively increased with the increase of H₂S concentrations and exposure time. The liver-somatic index (LSI) and growth rate significantly decreased (p<0.05) with increased concentrations of H₂S and exposure time. Fulton's condition factor failed to predict (p>0.1) stress effects in fish exposed less than six weeks to H₂S. However, RNA-DNA ratios showed high correlations with H2S concentrations from the second (r²= 0.83; p<0.01) to sixth week (r²=0.98;p<0.01) of exposure. Thiosulphate and sulphaemoglobin showed positive correlations with H₂S concentrations (r²= 0.79; p<0.01 and r²= 0.89; p<0.01 respectively). Sulphur accumulation in gills was positively correlated with thiosulphate and sulphaemoglobin concentrations in blood (r²= 0.74; p<0.01), indicating that these compounds resulted from H2S exposure. In addition, H2S levels in water were directly correlated with GST activities and sulphaemoglobin concentrations. However, H2S concentrations showed an inverse relationship with oxyhaemoglobin concentrations. The field study supported the laboratory findings for two indicators; thiosulphate and sulphur accumulation, were potential biological markers for H₂S toxicity. Other markers such as Fulton' s condition factor, liver-somatic index, growth rate, RNA-DNA ratio, histopathology and histochemistry did not reflect specific toxic effect, although they can be used to indicate the general health condition of fish exposed to H₂S. Among all the indicators, thiosulphate was found to be the simplest and fastest biological marker for detecting H₂S toxicity.